A new trick for an old dog: The application of mifepristone in the treatment of adenomyosis. Issue 2 (8th December 2019) - Che, Xuan; Wang, Jianzhang; He, Jiayi; Yu, Qin; Sun, Wenting; Chen, Shuyi; Zou, Gen; Li, Tiantian; Guo, Xinyue; Zhang, Xinmei
Abstract: Adenomyosis is also called internal endometriosis and affects about 20% of reproductive‐aged women. It seriously reduces life quality of patients because current drug therapies face with numerous challenges. Long‐term clinical application of mifepristone exhibits wonderful therapeutic effects with mild side‐effects in many disorders since 1982. Since adenomyosis is a refractory disease, we investigate whether mifepristone can be applied in the treatment of adenomyosis. In this study, we investigated the direct effects of mifepristone on human primary eutopic endometrial epithelial cells and stromal cells in adenomyosis. We found that mifepristone causes cell cycle arrest through inhibiting CDK1 and CDK2 expressions and induces cell apoptosis via the mitochondria‐dependent signalling pathway in endometrial epithelial cells and stromal cells of adenomyosis. Furthermore, mifepristone inhibits the migration of endometrial epithelial cells and stromal cells through decreasing CXCR4 expression and restricts the invasion of endometrial epithelial cells via suppression of epithelial‐mesenchymal transition in adenomyosis. We also found that mifepristone treatment decreases the uterine volume, CA125 concentration and increases the haemoglobin concentration in serum for adenomyosis patients. Therefore, we demonstrate that mifepristone could serve as a novel therapeutic drug in the treatment of adenomyosis, and therefore, the old dog can do a new trick.